Metabolic Score for Insulin Resistance (METS-IR) Associations with Subclinical Left Ventricular and Left Atrial Remodelling in Young Subjects with Hypertension - Ezhova, Nadezhda E.; Shavarova, Elena K.; Kobalava, Zhanna D.; Bazdyreva, Elena I.; Shavarov, Andrey A. (Annals of Clinical Cardiology, 2024)
Abstract Background: Insulin resistance (IR) is associated with left ventricular (LV) remodeling and eventually leads to cardiovascular events. Recently elaborated metabolic score for IR (METS-IR) is one of noninsulin-based scores for insulin sensitivity estimation. In previous studies, METS-IR was predictive for incident type 2 diabetes, hypertension, and arterial stiffness. Associations of METS-IR with subclinical myocardial damage were discussed in a few works. Objective: The objective of the study was to investigate relationship between IR estimated with METS-IR and early heart remodeling in young patients with hypertension. Methods: We included 96 hypertensive subjects free of diabetes mellitus aged 18-45 years in prospective cross-sectional study. In each patient, we estimated IR with homeostasis model assessment-estimated IR (HOMA-IR) and METS-IR scores, performed ambulatory blood pressure monitoring and echocardiography including 2D speckle-tracking. Results: Patients with the highest METS-IR quartile had significantly higher left ventricular mass index (LVMI) and differed from patients with lower METS-IR score in some of the diastolic function characteristics but not in LV global longitudinal strain. METS-IR had stronger correlation with most of the echocardiographic features of abnormal LV geometry and function, including LVMI, relative wall thickness, e', E/e', tricuspid regurgitation velocity, left atrial (LA) volume index, and LV global longitudinal strain, than HOMA-IR. In multiple regression analysis METS-IR was independently associated with LVMI (B = 0.80 [0.37; 1.22], P < 0.0001) and LA reservoir stain (LARs) (B = −0.40 (−0.57; −0.23), P < 0.0001). Conclusion: Noninsulin-based index of IR METS-IR is independently associated with LV and LA remodeling in young subjects with hypertension.